ABCC1 transporter exports the immunostimulatory cyclic dinucleotide cGAMP - Maltbaek, Joanna H.; Cambier, Stephanie; Snyder, Jessica M.; Stetson, Daniel B. (Immunity (Cambridge, Mass.), 2022)
The DNA sensor cyclic GMP-AMP synthase (cGAS) is important for antiviral and anti-tumor immunity. cGAS generates cyclic GMP-AMP (cGAMP), a diffusible cyclic dinucleotide that activates the antiviral response through the adaptor protein stimulator of interferon genes (STING). cGAMP cannot passively cross cell membranes, but recent advances have established a role for extracellular cGAMP as an “immunotransmitter” that can be imported into cells. However, the mechanism by which cGAMP exits cells remains unknown. Here, we identifed ABCC1 as a direct, ATP-dependent cGAMP exporter in mouse and human cells. We show that ABCC1 overexpression enhanced cGAMP export and limited STING signaling and that loss of ABCC1 reduced cGAMP export and potentiated STING signaling. We demonstrate that ABCC1 deficiency exacerbated cGAS-dependent autoimmunity in the Trex1−/− mouse model of Aicardi-Goutières syndrome. Thus, ABCC1-mediated cGAMP export is a key regulatory mechanism that limits cell-intrinsic activation of STING and ameliorates STING-dependent autoimmune disease. •The immunostimulatory molecule cGAMP is actively exported from live cells•ABCC1 mediates active, ATP-dependent cGAMP export•ABCC1-mediated cGAMP export limits activation of the STING-interferon pathway•ABCC1 limits cGAS-dependent autoimmunity in vivo Cyclic GMP-AMP (cGAMP) is an “immunotransmitter” that can be imported into cells to activate antiviral responses, but how cGAMP exits cells is currently unknown. Maltbaek et al. identify ABCC1 as an active cGAMP exporter that modulates STING-dependent immunity.